Technologies of Selective Energy Supply at Evaporation of Food Solutes - Burdo O.G.; Burdo A.K.; Sirotyuk I.V.; Pour D.R. (Problems of the Regional Energetics)
The aim of the research is to create innovative evaporating equipment that can produce concentrates with a high content of solids, with a low level of thermal effects on raw materials. The significance of the solution of technological problems of the key process of food technologies - concentration of liquid solutions (juices, extracts, etc.) is shown. Problems and scientific contradictions are formulated and the hypothesis on using of electromagnetic energy sources for direct energy transfer to solution’s moisture has been offered. The prospects of such an energy effect are proved by the energy management methods. The schemes of fuel energy conversion for the conventional thermal concentration technology and the innovative plant based on the electromagnetic energy generators are presented. By means of the similarity theory the obtained model is transformed to the criterial one depicted kinetic of evaporation process at the electromagnetic field action. The dimensionless capacity of the plant is expressed by the dependence between the Energetic effect number and relative moisture content. The scheme of automated experimental system for study of the evaporation process in the microwave field is shown. The experimental results of juice evaporation are presented. It has been demonstrated that the technologies of selective energy supply represent an effective tool for improvement of juice concentration evaporative plants. The main result of the research is design of the evaporator that allows reaching juice concentrates with °brix 95 at the temperature as low as 35 °С, i.e. 2…3 times superior than traditional technologies.